Hydrogenation of furfural over supported Pd catalysts - Torres Bujalance, Virginia; Cecilia-Buenestado, Juan Antonio; Jiménez-Gómez, Carmen Pilar; García-Sancho, Cristina; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús (My University, 2018)
Lignocellulosic biomass is the most abundant and economical non-fossil carbon source. Furthermore, it is not competitive with the food chain, coming from lignocellulosic wastes including agricultural and food processing, local urban solid and forestry wastes. However, these are made up of complex carbohydrates (mainly, cellulose and hemicellulose), which require to be broken down in their respective monomers. The hemicellulose is mainly composed of pentosans, which, after an initial hydrolysis step, are dehydrated to furfural. Furfural is an important platform molecule, since it has a wide range of applications, being considered the main chemical, aside from bioethanol, obtained from the sugar platform for the synthesis of chemicals, for plastics, agrochemical and pharmaceutical industries. In the present work, the hydrogenation of furfural in gas phase has been studied by using Pd as active phase, and different metal oxides as support, in order to elucidate the influence of the support on the catalytic performance. Furfural can be converted into chemicals with important applications in many different industrial fields. Thus, reduction of furfural can proceed through different pathways depending on the experimental conditions, where the nature of the catalysts plays a key role. In the case of Pd-based catalysts, the main products come from the decarbonylation of furfural.The catalytic results reveals that the nature of the support exerts an important influence on furfural conversion and yield. The highest conversion (92% after 5 h of TOS at 463 K) was attained with a Pd-SiO2 catalyst, with a furan yield of 70 mol%. This catalyst is the most selective to furan and a moderate deactivation is only observed after 5 h reaction. The catalytic performance demonstrates that decarbonylation reaction was the main pathway, although the formation of furfuryl alcohol and 2-methylfuran also suggests that the hydrogenation of the carbonyl group of furfural takes place.
Keywords: Biomasa - Congresos; Palladium; Biomass; Heterogeneous catalysis; Hydrogenation